(3aJM GdhgGH TQM efgL GdWdGHs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s
(3ChdgG (B:s
(3hjHOC ef cJGH GdHjY YfO bhdg (B: (3jWdb GdHjY Ydi bSje GdTQGA hgh Jedjc HKef Ydi hLg eNUhU hGdTQGA Jedc HPdc hYdi GdYbO GdeQcH efgeG hgh GdeQGO HGdJQLeIs
(3BNQgG (B:s
(3hjfJgj YfO cJGH GdLYGdI (B- (3YfO bhdg (B: ( (3hMda edJRe CfcQ TQW LYd ChQGOG (B) (3ajUOb dCf GdCUd YOeg aEf GNJdaG HYO GSJMbGb aj bOQ LYd Ch bOQ eQOhO JMGdaG ddYGed CLQI GdeKd ceG Yde ef HGH GdGNJdGa aj cjajI GdYbO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 46s
(3eYLe GdeDdajf (B1 / 733s
(3cTa GdXfhf (B2 / 1875s
(3TPQGJ GdPgH (B8 / 134s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs